Chinese "agricultural diplomacy" in Africa: a sketch of an analysis of an atypical form of "Land Grab" - (:unkn) unknown (My University, 2023)
The thousand-year-old link between China and Africa has enjoyed a privileged position in Chinese diplomacy since the proclamation of the People‟s Republic of China in 1949. The African continent is considered both a field of experimentation and a privileged place to stage the "Chinese dream" of exporting a socialist development model. Indeed, China is building relationships with African peoples through intense public diplomacy. From buying vineyards and agribusiness factories to building agricultural demonstration centres in Africa, Chinese agricultural investment takes many forms. China is reportedly grabbing millions of hectares of land in Africa to secure its food needs. The term "land grabbing" was coined in 2008 to describe the controversial acquisition of large tracts of agricultural land by transnational corporations and governments. The technique was successfully used by the United States in the 19th century to build its nationhood, then by European nations to build their fragile colonial empires, and then by American tycoons on millions of hectares in the Amazon for projects, all of which have gone bankrupt. The Chinese land grab in Africa is political nonsense and economic nonsense, false news used to denigrate a country. Welcomed with open arms by some farmers who see in it the promise of new commercial outlets or experienced by others as a grabbing of resources, China‟s interest in the agricultural and agri-food sectors, which has been particularly strong since 2009, proves their highly strategic nature. There has been talking for some years of Chinese actors buying up agricultural land in Africa. Such investments are often referred to by the expression Land Grab, which immediately suggests aggression. It is nothing less than an assault on African land. How can this Land Grab be defined? What is the place of the Chinese Land Grab in Africa? With such an objective in mind, it seems appropriate to consider the nature of the Chinese Land G
Keywords: African Research